A shared data approach more accurately represents the rates and patterns of violence with injury assaults. Issue 12 (22nd October 2017) - Gray, Benjamin J; Barton, Emma R; Davies, Alisha R; Long, Sara J; Roderick, Janine; Bellis, Mark A
Abstract : Background: To investigate whether sharing and linking routinely collected violence data across health and criminal justice systems can provide a more comprehensive understanding of violence, establish patterns of under-reporting and better inform the development, implementation and evaluation of violence prevention initiatives. Methods: Police violence with injury (VWI) crimed data and emergency department (ED) assault attendee data for South Wales were collected between 1 April 2014 and 31 March 2016 to examine the rates and patterns of VWI. Person identifiable data (PID) were cross-referenced to establish if certain victims or events were less likely to be reported to criminal justice services. Results: A total of 18 316 police crimed VWI victims and 10 260 individual ED attendances with an assault-related injury were considered. The majority of ED assault attendances (59.0%) were unknown to police. The key demographic identified as under-reporting to police were young males aged 18–34 years, while a significant amount of non-reported assaults involved a stranger. The combined monthly age-standardised rates were recalculated and on average were 74.7 (95% CI 72.1 to 77.2) and 66.1 (95% CI 64.0 to 68.2) per 100 000 population for males and females, respectively. Consideration of the additional ED cases resulted in a 35.3% and 18.1% increase on the original police totals for male and female VWI victims. Conclusions: This study identified that violence is currently undermeasured, demonstrated the importance of continued sharing of routinely collected ED data and highlighted the benefits of using PID from a number of services in a linked way to provide a more comprehensive picture of violence.